Uma análise das práticas de avaliação dos professores na multissérie do ensino fundamental da escola do campo Joana da Conceição Lima, no município de Abaetetuba - CARNEIRO, Valdecira Cavalcante (2024)
This work aimed to study the evaluation practices carried out by teachers in the multiseries classes. The locus of the research is the school Joana da Conceição Lima, which is located in the Brasília branch, in the community Nossa Senhora do Bom Remédio. For the development of the work, the teachers working in the multiseries were taken with research subjects, in order to obtain information about the school reality and the evaluation process carried out. In order to reach this proposal, the methodology of qualitative research and case study was adopted, through bibliographical researches, consultations to academic papers related to the subject and questionnaire application to teachers with semi-structured questions, which allow a greater flexibility of responses.